AB0929 THE IMPACT OF KINESIOPHOBIA ON GAIT KINEMATICS IN PATIENTS WITH SPONDYLOARTHROPATHIES - Schweiger, Isabella; Koschinsky, J.; Elie-Tino, Godonou; Tascilar, Koray; Coppers, Birte; Kleyer, Arnd; Morf, Harriet; Simon, David; Bayat, Sara; Bohr, Daniela; Valor, L.; Raimondo, Maria Gabriella; et al. (Annals of the Rheumatic Diseases, 2024)
Background: In light of much needed functional assessments to monitor disease activity and functional status in spondyloarthritis (SpA), gait analysis is gaining interest. While it is generally known that the functional status and gait kinematics are closely related, it is unclear how fear of movement (kinesiophobia) affects gait kinematics in SpA patients. Objectives: To assess the influence of kinesiophobia on gait kinematics in patients with SpA and how sex mediates this relationship. Methods: A standardized 2-minute walk with self-selected walking speed was performed with 104 patients (psoriatic arthritis (PsA, CASPAR criteria) and ankylosing spondylitis (axSpa, ASAS criteria) (Internal Medicine 3 outpatient clinics Erlangen, Germany) in the hospital hallway. Spatio-temporal gait parameters (number of analyzed steps, cadence, gait velocity, double stance length and duration, swing left and right, stance left and right, temporal and spatial gait cycle variability) were recorded using the inertial sensor system RehaGait® (Hasomed, Magdeburg, Germany) and sagittal joint angles were computed and analyzed via MATLAB [1] (of the whole gait cycle the maximal and minimal flexion angle of left and right hip, knee, ankle). Patient characteristics and clinical assessments were retrieved from the patients record on the day of the gait analysis. Additionally, patients were asked to fill out the tampa scale of kinesiophobia (TSK) and an anamnestic questionnaire. Multivariate multiple linear regression was used to investigate the relationship between TSK score and kinematic gait parameters; mediation analysis was computed with sex as the control variable (potential mediator). Results: Patients characteristics of the 104 participants in this study are summarized in Table 1. Kinesiophobia affected the mediator sex (0.039; CI (0.005, 0.074), p=0.026) and the effect of kinesiophobia on gait kinematics differs between sexes. When controlling for the TSK score, male subjects took fewer steps and had a longer stance length. This may be due to them being taller (female: 166.6 cm, male: 179.9 cm; p<0.001). When controlling for sex, kinesiophobia is significantly associated with gait velocity (Coef: -0.009, p=0.003), double stance length (Coef: -0.005, p=0.031), double stance duration (Coef: 0.004, p=0.007), cadence (Coef: -0.39, p=0.006), swing phase left (Coef: -0.089, p=0.006) and the minimal left knee angle (Coef: -0.002, p=0.046). Conclusion: Patients with higher fear of movement scores by TSK walked slower, had a lower cadence, took smaller steps and had an increased extension of the left knee. While previous studies [2, 3] reported a decreased range of motion in axSpa patients compared to healthy subjects our results suggest that this can not only result from disease status itself, but that gait kinematics are associated with fear of movement. This is important to consider when gait analysis is used to assess the effect of interventions on functional status in SpA patient

An AI-Powered Clinical Decision Support System to Predict Flares in Rheumatoid Arthritis: A Pilot Study - Labinsky, Hannah; Ukalovic, Dubravka; Hartmann, Fabian; Runft, Vanessa; Wichmann, Andre; Jakubcik, Jan; Gambel, Kira; Otani, Katharina; Morf, Harriet; Taubmann, Jule; Fagni, Filippo; Kleyer, Arnd; et al. (Diagnostics, 2023)
Treat-to-target (T2T) is a main therapeutic strategy in rheumatology; however, patients and rheumatologists currently have little support in making the best treatment decision. Clinical decision support systems (CDSSs) could offer this support. The aim of this study was to investigate the accuracy, effectiveness, usability, and acceptance of such a CDSS-Rheuma Care Manager (RCM)-including an artificial intelligence (AI)-powered flare risk prediction tool to support the management of rheumatoid arthritis (RA). Longitudinal clinical routine data of RA patients were used to develop and test the RCM. Based on ten real-world patient vignettes, five physicians were asked to assess patients' flare risk, provide a treatment decision, and assess their decision confidence without and with access to the RCM for predicting flare risk. RCM usability and acceptance were assessed using the system usability scale (SUS) and net promoter score (NPS). The flare prediction tool reached a sensitivity of 72%, a specificity of 76%, and an AUROC of 0.80. Perceived flare risk and treatment decisions varied largely between physicians. Having access to the flare risk prediction feature numerically increased decision confidence (3.5/5 to 3.7/5), reduced deviations between physicians and the prediction tool (20% to 12% for half dosage flare prediction), and resulted in more treatment reductions (42% to 50% vs. 20%). RCM usability (SUS) was rated as good (82/100) and was well accepted (mean NPS score 7/10). CDSS usage could support physicians by decreasing assessment deviations and increasing treatment decision confidence.
CRIS-Team WoS Importer:2023-01-27

A Yoga Exercise App Designed for Patients With Axial Spondylarthritis: Development and User Experience Study - Truong, Minh Tam; Nwosu, Obioma Bertrand; Gaytan Torres, Maria Elena; Segura Vargas, Maria Paula; Seifer, Ann-Kristin; Nitschke, Marlies; Ibrahim, Alzhraa; Knitza, Johannes; Krusche, Martin; Eskofier, Björn; Schett, Georg; Morf, Harriet (JMIR Formative Research, 2022)
Background: Besides anti-inflammatory medication, physical exercise represents a cornerstone of modern treatment for patients with axial spondyloarthritis (AS). Digital health apps (DHAs) such as the yoga app YogiTherapy could remotely empower patients to autonomously and correctly perform exercises. Objective: This study aimed to design and develop a smartphone-based app, YogiTherapy, for patients with AS. To gain additional insights into the usability of the graphical user interface (GUI) for further development of the app, this study focused exclusively on evaluating users’ interaction with the GUI. Methods: The development of the app and the user experience study took place between October 2020 and March 2021. The DHA was designed by engineering students, rheumatologists, and patients with AS. After the initial development process, a pilot version of the app was evaluated by 5 patients and 5 rheumatologists. The participants had to interact with the app’s GUI and complete 5 navigation tasks within the app. Subsequently, the completion rate and experience questionnaire (attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty) were completed by the patients. Results: The results of the posttest questionnaires showed that most patients were already familiar with digital apps (4/5, 80%). The task completion rates of the usability test were 100% (5/5) for the tasks T1 and T2, which included selecting and starting a yoga lesson and navigating to an information page. Rheumatologists indicated that they were even more experienced with digital devices (2/5, 40% experts; 3/5, 60% intermediates). In this case, they scored task completion rates of 100% (5/5) for all 5 usability tasks T1 to T5. The mean results from the User Experience Questionnaire range from −3 (most negative) to +3 (most positive). According to rheumatologists’ evaluations, attractiveness (mean 2.267, SD 0.401) and stimulation (mean 2.250, SD 0.354) achieved the best mean results compared with dependability (mean 2.000, SD 0.395). Patients rated attractiveness at a mean of 2.167 (SD 0.565) and stimulation at a mean of 1.950 (SD 0.873). The lowest mean score was reported for perspicuity (mean 1.250, SD 1.425). Conclusions: The newly developed and tested DHA YogiTherapy demonstrated moderate usability among rheumatologists and patients with rheumatic diseases. The app can be used by patients with AS as a complementary treatment. The initial evaluation of the GUI identified significant usability problems that need to be addressed before the start of a clinical evaluation. Prospective trials are also needed in the second step to prove the clinical benefits of the ap

Back on track – digital health applications to treat back pain of rheumatic patients? Results of a qualitative interview study - Boy, Katharina; May, Susann; Labinsky, Hannah; Morf, Harriet; Heinze, Martin; Leipe, Jan; Kuhn, Sebastian; Schett, Georg; Knitza, Johannes; Muehlensiepen, Felix (Rheumatology International, 2024)
Non-specific low back pain (NLBP) is prevalent among patients with rheumatic conditions. Digital health applications (DiGAs) provide reimbursed, personalized home treatment for patients, promising to overcome limitations of traditional healthcare systems. However, the adoption and effectiveness of back pain-specific DiGAs in rheumatology are not well understood. This study aims to explore the experiences and perspectives of a diverse group of rheumatology stakeholders regarding the use of DiGAs for back pain management. Qualitative interviews and a focus group discussion were conducted with a wide range of stakeholders including rheumatic patients, rheumatologists, nurses and DiGA producers. The data were analysed using qualitative content analysis. The study included 15 interviews (10 rheumatic patients, 4 rheumatologists, 1 DiGA producer) and 1 focus group with mixed participants (n = 12). Most stakeholders valued the instant access to personalized and effective back pain treatment provided by DiGAs. Patients appreciated the flexibility and ease of use of DiGAs which can be used anywhere and anytime. Concerns were raised about insufficient guidance regarding correct execution of exercises, which was seen as potentially dangerous and unsettling for patients. Healthcare professionals (HCPs) highlighted barriers, such as the lack of reimbursement, time constraints, and inadequate DiGA-specific education as barriers to prescribing DiGAs. Additionally, poor patient onboarding often led to delays, increased skepticism, and premature discontinuation of therapy. Stakeholders emphasized the challenges of current care driven by a shortage of HCPs and generally supported usage of back pain DiGAs. Various barriers and solution approaches were identified to enhance the performance, usability, and implementation of DiGAs in rheumatology.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Digital health applications; eHealth; DTx; digital treatment; telemedicine; Implementation science; Non specific low back pain; Rheumatology

Competencies for health-enhancing physical activity are associated with body mass: results of an updated data pooling across 18 samples - Carl, Johannes; Zheng, Miaobing; Popp, Johanna; Eckert, Katharina; Geidl, Wolfgang; Blaschke, Simon; Schmid, Julia; Grüne, Eva; Oppermann, Leonard; Liphardt, Anna-Maria; Morf, Harriet; Weißenfels, Anja; et al. (Obesity, 2024)
Objective: Although previous studies have illuminated associations between body mass and physical activity (PA), there have been scant insights regarding the physical, cognitive, and motivational determinants of PA in relationship to body mass. This study aimed to model courses of competencies for health-enhancing PA across the spectrum of BMI. Methods: We used cross-sectional data of 3670 individuals (mean [SD]: BMI, 25.54 [5.71] kg/m2; age, 46.11 [14.96] years) from a large data pooling with 18 primary samples employing the PA-related health competence (PAHCO) instrument. ANCOVA determined differences in 10 PAHCO indicators by BMI categories (underweight, normal weight, overweight, and obesity). Covariate-adjusted multilevel models described the nonlinear courses of the PAHCO indicators across the BMI spectrum. Results: The levels of all 10 PAHCO indicators differed significantly among the BMI categories (F ≥ 14.8; p < 0.001). All competencies for health-enhancing PA could be best described by cubic functions having their maximum around normal weight while regressing with underweight and with increasing grades of obesity (0.02 ≤ (Formula presented.) ≤ 0.31). Conclusions: This study adds to associations between BMI and PA levels by specifying individuals' multidimensional requirements for health-enhancing PA. The present findings call for an integration of physical, motivational, and cognitive factors in practices of PA promotion and sustainable obesity treatment.
CRIS-Team Scopus Importer:2024-10-04

Complementary App-Based Yoga Home Exercise Therapy for Patients With Axial Spondyloarthritis: Usability Study - Grube, Lara; Petit, Pascal; Vuillerme, Nicolas; Nitschke, Marlies; Nwosu, Obioma Bertrand; Knitza, Johannes; Krusche, Martin; Seifer, Ann-Kristin; Eskofier, Björn; Schett, Georg; Morf, Harriet (JMIR Formative Research, 2024)
Background: Axial spondyloarthritis (AS) is a chronic inflammatory rheumatic disease characterized by potentially disabling inflammation of the spine and adjacent joints. Regular exercise is a cornerstone of treatment. However, patients with AS currently have little support. YogiTherapy (MaD Lab) is an app developed to support patients with AS by providing instructions for yoga-based home exercise therapy. Objective: This study aimed to evaluate the usability and acceptance of the newly designed YogiTherapy app for patients with AS. Methods: Patients completed the User Version of the Mobile Application Rating Scale (uMARS) and net promoter score (NPS) questionnaires after the app introduction. Wilcoxon Mann-Whitney rank sum test, chi-square test for count data, and correlation analysis were conducted to examine the usability of the app, acceptance, and patient characteristics. Results: A total of 65 patients with AS (33, 51% female; age: mean 43.3, SD 13.6 years) were included in the study from May 2022 to June 2023. Subsequently, the data were analyzed. Usability was rated moderate, with a mean uMARS of 3.35 (SD 0.47) points on a scale from 0 to 5. The highest-rated uMARS dimension was information (mean 3.88, SD 0.63), followed by functionality (mean 3.84, SD 0.87). Females reported a significantly higher uMARS total score than males (mean 3.47, SD 0.48 vs mean 3.23, SD 0.45; P=.03, Vargha and Delaney A [VDA] 0.66, 95% CI 0.53-0.77). The mean average of the NPS was 6.23 (SD 2.64) points (on a scale from 0 to 10), based on 43% (26/65 nonpromoters, 42% (25/65) indifferent, and 15% (9/65) promoters. A total of 7% (5/65) of those surveyed did not answer the question. When applying the NPS formula, the result is –26%. The NPS showed a positive correlation with the usage of mobile apps (r=0.39; P=.02). uMARS functionality was significantly higher rated by patients younger than 41 years (mean 4.17, SD 0.55 vs mean 3.54, SD 1; P<.001; VDA 0.69, 95% CI 0.56-0.80). Patients considering mobile apps as useful reported higher uMARS (r=0.38, P=.02). The uMARS app quality mean score was correlated with the frequency of using apps (r=–0.21, P<.001). Conclusions: The results revealed moderate acceptance and usability ratings, prompting further app improvement. Significant differences were observed between age and gender. Our results emphasize the need for further improvements in YogiTherapy.
CRIS-Team Scopus Importer:2024-10-04
Keywords: adjacent joints; ankylosing spondylitis; app; apps; axial spondylarthritis; chronic; correlation analysis; DHA; digital health application; digital therapeutics; DTx; eHealth; exercise; home exercise; joint; joints; patient; patient acceptance; patients; physical exercise; rheumatic disease; self-assessment; spine; spondyloarthritis; therapy; usability; usability study; Yoga; YogiTherapy

Correction to: Back on track – digital health applications to treat back pain of rheumatic patients? Results of a qualitative interview study (Rheumatology International, (2024), 10.1007/s00296-024-05726-x) - Boy, Katharina; May, Susann; Labinsky, Hannah; Morf, Harriet; Heinze, Martin; Leipe, Jan; Kuhn, Sebastian; Schett, Georg; Knitza, Johannes; Muehlensiepen, Felix (Rheumatology International, 2024)
In this article Figs. 1 and 2 were wrongly numbered; Fig. 1 should have been Fig. 2 and vice versa as shown below. Summary of perceived advantages and strenghts of back pain DiGAs Summary of observed implementation barriers and potential approaches to overcome them, categorized into four dimensions: patients, healthcare professionals, technology, and the healthcare system The original article has been corrected.
CRIS-Team Scopus Importer:2024-12-06

Diagnostic Accuracy of a Mobile AI-Based Symptom Checker and a Web-Based Self-Referral Tool in Rheumatology: Multicenter Randomized Controlled Trial - Knitza, Johannes; Tascilar, Koray; Fuchs, Franziska; Mohn, Jacob; Kuhn, Sebastian; Bohr, Daniela; Muehlensiepen, Felix; Bergmann, Christina; Labinsky, Hannah; Morf, Harriet; Araujo, Elizabeth; Englbrecht, Matthias; et al. (Journal of Medical Internet Research, 2024)
Background: The diagnosis of inflammatory rheumatic diseases (IRDs) is often delayed due to unspecific symptoms and a shortage of rheumatologists. Digital diagnostic decision support systems (DDSSs) have the potential to expedite diagnosis and help patients navigate the health care system more efficiently. Objective: The aim of this study was to assess the diagnostic accuracy of a mobile artificial intelligence (AI)–based symptom checker (Ada) and a web-based self-referral tool (Rheport) regarding IRDs. Methods: A prospective, multicenter, open-label, crossover randomized controlled trial was conducted with patients newly presenting to 3 rheumatology centers. Participants were randomly assigned to complete a symptom assessment using either Ada or Rheport. The primary outcome was the correct identification of IRDs by the DDSSs, defined as the presence of any IRD in the list of suggested diagnoses by Ada or achieving a prespecified threshold score with Rheport. The gold standard was the diagnosis made by rheumatologists. Results: A total of 600 patients were included, among whom 214 (35.7%) were diagnosed with an IRD. Most frequent IRD was rheumatoid arthritis with 69 (11.5%) patients. Rheport’s disease suggestion and Ada’s top 1 (D1) and top 5 (D5) disease suggestions demonstrated overall diagnostic accuracies of 52%, 63%, and 58%, respectively, for IRDs. Rheport showed a sensitivity of 62% and a specificity of 47% for IRDs. Ada’s D1 and D5 disease suggestions showed a sensitivity of 52% and 66%, respectively, and a specificity of 68% and 54%, respectively, concerning IRDs. Ada’s diagnostic accuracy regarding individual diagnoses was heterogenous, and Ada performed considerably better in identifying rheumatoid arthritis in comparison to other diagnoses (D1: 42%; D5: 64%). The Cohen κ statistic of Rheport for agreement on any rheumatic disease diagnosis with Ada D1 was 0.15 (95% CI 0.08-0.18) and with Ada D5 was 0.08 (95% CI 0.00-0.16), indicating poor agreement for the presence of any rheumatic disease between the 2 DDSSs. Conclusions: To our knowledge, this is the largest comparative DDSS trial with actual use of DDSSs by patients. The diagnostic accuracies of both DDSSs for IRDs were not promising in this high-prevalence patient population. DDSSs may lead to a misuse of scarce health care resources. Our results underscore the need for stringent regulation and drastic improvements to ensure the safety and efficacy of DDSSs.
CRIS-Team Scopus Importer:2024-08-02
Keywords: artificial intelligence; decision; decision support; decision support system; diagnosis; diagnostic; diagnostic decision support system; eHealth; randomized controlled trial; resources; rheumatologists; rheumatology; support; support system; symptom assessment; symptom checker; tool

Diagnostic delay stages and pre-diagnostic treatment in patients with suspected rheumatic diseases before special care consultation: results of a multicenter-based study - Fuchs, Franziska; Morf, Harriet; Mohn, Jacob; Muehlensiepen, Felix; Ignatyev, Yuriy; Bohr, Daniela; Araujo, Elizabeth; Bergmann, Christina; Simon, David; Kleyer, Arnd; Vorbrueggen, Wolfgang; Ramming, Andreas; et al. (Rheumatology International, 2022)
Early and effective discrimination (triage) of patients with inflammatory rheumatic diseases (IRD) and other diseases (non-IRD) is essential for successful treatment and preventing damage. The aim of this study was to investigate diagnostic delays and pre-diagnosis treatment in patients newly presenting to rheumatology outpatient clinics. A total of 600 patients newly presenting to one university hospital and two non-academic centers were included. Time from onset of symptoms to rheumatology consultation “total delay” as well as medical treatment before consultation were recorded. Median time from symptom onset to rheumatologist appointment (total delay) was 30 weeks. Median time to online search, first physician appointment request and first physician appointment was 2, 4 and 5 weeks, respectively. Total delay was significantly shorter for IRD patients compared to non-IRD patients, 26 vs 35 weeks (p = 0.007). Only 17.7% of all patients and 22.9% of IRD patients had a delay of less than 12 weeks. Total delay was significantly lower in patients seen in non-academic centers compared to the university center, 20 vs 50 weeks (p < 0.0001). 32.2% of IRD patients received medical treatment that eased their symptoms prior to the rheumatology appointment. These findings highlight the persistent diagnostic delays in rheumatology; however, they also suggest that current triage strategies effectively lead to earlier appointments for IRD patients. Improvement of triage methods and pre-diagnosis treatment could decrease overall burden of disease in IRD patients.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Delayed diagnosis; Diagnostic delay; Health service research; Outcome research; Time to therapy; Triage

German Version of the Telehealth Usability Questionnaire and Derived Short Questionnaires for Usability and Perceived Usefulness in Health Care Assessment in Telehealth and Digital Therapeutics: Instrument Validation Study - Zimmermann, Jannik; Morf, Harriet; Scharf, Florian; Knitza, Johannes; Moeller, Heidi; Muehlensiepen, Felix; Nathrath, Michaela; Orlemann, Till; Voelker, Thomas; Deckers, Merlin (JMIR Human Factors, 2024)
Background: The exponential growth of telehealth is revolutionizing health care delivery, but its evaluation has not matched the pace of its uptake. Various forms of assessment, from single-item to more extensive questionnaires, have been used to assess telehealth and digital therapeutics and their usability. The most frequently used questionnaire is the “Telehealth Usability Questionnaire” (TUQ). The use of the TUQ is limited by its restricted availability in languages other than English and its feasibility. Objective: The aims of this study were to create a translated German TUQ version and to derive a short questionnaire for patients-“Telehealth Usability and Perceived Usefulness Short Questionnaire for patients” (TUUSQ). Methods: As a first step, the original 21-item TUQ was forward and back-translated twice. In the second step, 13 TUQ items were selected for their suitability for the general evaluation of telehealth on the basis of expert opinion. These 13 items were surveyed between July 2022 and September 2023 in 4 studies with patients and family members of palliative care, as well as patients with chronic autoimmune diseases, evaluating 13 health care apps, including digital therapeutics and a telehealth system (n1=128, n2=220, n3=30, and n4=12). Psychometric exploratory factor analysis was conducted. Results: The analysis revealed that a parsimonious factor structure with 2 factors (“perceived usefulness in health care” and “usability”) is sufficient to describe the patient’s perception. Consequently, the questionnaire could be shortened to 6 items without compromising its informativeness. Conclusions: We provide a linguistically precise German version of the TUQ for assessing the usability and perceived usefulness of telehealth. Beyond that, we supply a highly feasible shortened version that is versatile for general use in telehealth, mobile health, and digital therapeutics, which distinguishes between the 2 factors “perceived usefulness in health care” and “usability” in patients.
CRIS-Team Scopus Importer:2025-02-04
Keywords: autoimmune chronic diseases; digital therapeutics; feasibility; German; mHealth; mobile health; Net Promoter Scale; NPS; questionnaire; questionnaire translation; questionnaire validation; technology acceptance model; telehealth; therapeutics; usability; usefulness; validity

Impact of the digital health application ViViRA on spinal mobility, physical function, quality of life and pain perception in spondyloarthritides patients: a randomized controlled trial - Palm von Alten Blaskowitz, Paloma Alexandra; Liphardt, Anna-Maria; Bouzas, Claudia; Coppers, Birte; Petit, Pascal; Vuillerme, Nicolas; Bundle, Vanessa; Rudolf, Sebastian; Knitza, Johannes; Raimondo, Maria Gabriella; Labinsky, Hannah; Hatscher, Lukas; et al. (Arthritis Research & Therapy, 2024)
Background: Spondyloarthritides (SpAs) are a group of common rheumatic diseases that often cause limited mobility and lower back pain. Physiotherapy is an integral part of treatment, but access to physiotherapy limits treatment success. Digital health applications (DHAs) enable home-based physiotherapy and could significantly improve access for SpAs patients. The aim is to investigate the clinical effects of the DHA ViViRA compared with those of standard physiotherapy. Methods: SpAs patients with chronic back pain were enrolled in a randomized controlled trial. The intervention group received ViViRA DHA, whereas the control group received standard physiotherapy. Pain (verbal rating scale, PAIN-Detect), quality of life (SF-36) and mobility (BASMI) were assessed at baseline and after 12 weeks as the primary outcomes. Results: Data from 59 participants (71.2% female, mean age 45.2 years) were analyzed. The intervention group showed a significant improvement in mobility (average BASMI score: baseline: 1.1 [range 0.7–1.5]; follow-up: 1.0 [range 0.5–1.4]; p = 0.05), whereas the control group showed a significant decrease in mobility (baseline: 1.5 [range 1.1–1.9]; follow-up: 1.8 [range 1.4–2.2]; p = 0.00). The intervention group demonstrated lower pain intensity (VRS pain level at week 3.5 ± 2.8) than did the control group (VRS pain level at week 4.5 ± 2) after 12 weeks. Conclusion: Our results highlight the efficacy of DHAs such as ViViRA in the treatment of lower back pain in SpAs patients. Compared with the current gold standard, physiotherapy, DHA use results in superior outcomes. However, further larger studies are needed to confirm these promising results. Trial registration: The study is registered in the German clinical trial registry (DRKS) under the following ID: DRKS00031254.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DHA; Digital health application; E-Health; Mobility; Physical function; Psoriatic spondylitis; Spondyloarthritides; Spondyloarthropathy; ViViRA

PHOTOREALISTIC DEPICTION OF RHEUMATIC PATHOLOGIES BY CINEMATIC RENDERING FACILITATES DISEASE UNDERSTANDING OF PATIENTS WITH RHEUMATIC DISEASES - Pachowsky, Milena; Morf, Harriet; Simon, David; Schönau, Verena; Valor, L.; Knitza, Johannes; Engel, K.; Uder, Michael; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Refinement and Usability Analysis of an eHealth App for Ankylosing Spondylitis as a Complementary Treatment to Physical Therapy: Development and Usability Study - Nitschke, Marlies; Nwosu, Obioma Bertrand; Grube, Lara; Knitza, Johannes; Seifer, Ann-Kristin; Eskofier, Björn; Schett, Georg; Morf, Harriet (JMIR Formative Research, 2023)
Background: Mobile eHealth apps have been used as a complementary treatment to increase the quality of life of patients and provide new opportunities for the management of rheumatic diseases. Telemedicine, particularly in the areas of prevention, diagnostics, and therapy, has become an essential cornerstone in the care of patients with rheumatic diseases. Objective: This study aims to improve the design and technology of YogiTherapy and evaluate its usability and quality. Methods: We newly implemented the mobile eHealth app YogiTherapy with a modern design, the option to change language, and easy navigation to improve the app’s usability and quality for patients. After refinement, we evaluated the app by conducting a study with 16 patients with AS (4 female and 12 male; mean age 48.1, SD 16.8 y). We assessed the usability of YogiTherapy with a task performance test (TPT) with a think-aloud protocol and the quality with the German version of the Mobile App Rating Scale (MARS). Results: In the TPT, the participants had to solve 6 tasks that should be performed on the app. The overall task completion rate in the TPT was high (84/96, 88% completed tasks). Filtering for videos and navigating to perform an assessment test caused the largest issues during the TPT, while registering in the app and watching a yoga video were highly intuitive. Additionally, 12 (75%) of the 16 participants completed the German version of MARS. The quality of YogiTherapy was rated with an average MARS score of 3.79 (SD 0.51) from a maximum score of 5. Furthermore, results from the MARS questionnaire demonstrated a positive evaluation regarding functionality and aesthetics. Conclusions: The refined and tested YogiTherapy app showed promising results among most participants. In the future, the app could serve its function as a complementary treatment for patients with AS. For this purpose, surveys with a larger number of patients should still be conducted. As a substantial advancement, we made the app free and openly available on the iOS App and Google Play store
Keywords: ankylosing spondylitis; axial spondylarthritis; DHA; digital health application; eHealth; self-assessment; Usability; Yoga; YogiTherapy

Stepwise asynchronous telehealth assessment of patients with suspected axial spondyloarthritis: results from a pilot study - Labinsky, Hannah; von Rohr, Sophie; Raimondo, Maria Gabriella; Bohr, Daniela; Morf, Harriet; Horstmann, Britta; Seese, Felix; Proft, Fabian; Muehlensiepen, Felix; Boy, Katharina; Kuhn, Sebastian; Schmalzing, Marc; et al. (Rheumatology International, 2023)
Patients with axial spondyloarthritis (axSpA) suffer from one of the longest diagnostic delays among all rheumatic diseases. Telemedicine (TM) may reduce this diagnostic delay by providing easy access to care. Diagnostic rheumatology telehealth studies are scarce and largely limited to traditional synchronous approaches such as resource-intensive video and telephone consultations. The aim of this study was to investigate a stepwise asynchronous telemedicine-based diagnostic approach in patients with suspected axSpA. Patients with suspected axSpA completed a fully automated digital symptom assessment using two symptom checkers (SC) (bechterew-check and Ada). Secondly, a hybrid stepwise asynchronous TM approach was investigated. Three physicians and two medical students were given sequential access to SC symptom reports, laboratory and imaging results. After each step, participants had to state if axSpA was present or not (yes/no) and had to rate their perceived decision confidence. Results were compared to the final diagnosis of the treating rheumatologist. 17 (47.2%) of 36 included patients were diagnosed with axSpA. Diagnostic accuracy of bechterew-check, Ada, TM students and TM physicians was 47.2%, 58.3%, 76.4% and 88.9% respectively. Access to imaging results significantly increased sensitivity of TM-physicians (p < 0.05). Mean diagnostic confidence of false axSpA classification was not significantly lower compared to correct axSpA classification for both students and physicians. This study underpins the potential of asynchronous physician-based telemedicine for patients with suspected axSpA. Similarly, the results highlight the need for sufficient information, especially imaging results to ensure a correct diagnosis. Further studies are needed to investigate other rheumatic diseases and telediagnostic approaches.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Diagnosis; Health service research; Spondyloarthritis; Symptom checker; Telehealth; Telemedicine